Blood Profile of West African Dwarf (WAD) Goats Fed Cassava Peel Meal Based- Diets Supplemented with African Yambean Concentrate - I., Anya, M.; O., Ozung, P.; U., Okah; A, Ayuk, A.; A., Igwe, P. (Canadian Journal of Agriculture and Crops, 2018)
The blood profile of twenty (20) West African Dwarf bucks fed cassava peel meal based diets supplemented with varying levels of African yambean meal (AYBM) concentrate was investigated. Four diets were formulated with AYBM at 0, 10, 20 and 30 % levels designated as T1, T2, T3 and T4 respectively. Before the commencement of the study, a baseline status of the blood was established. Thereafter at the end of the study, the haematological and serum biochemical values were investigated to show if the difference existed principally due to the feedstuffs fed. Results showed that values for packed cell volume (PCV), haemoglobin concentration (Hb), red blood cell counts (RBCs) and white blood cell counts (WBCs) differed significantly (P< 0.05) between the respective diets. Average PCV value was highest in the control diet (T1) and least in diet T4 (30% YBSM). Serum biochemical values for total bilirubin (TB), serum urea, creatinine, total protein, cholesterol, glucose, serum glumate oxalotransaminase (SGOT) and serum glutamate pyruvatetransaminase (SGPT) differed significantly (P<0.05) between dietary treatments. The control diet had higher serum urea, but diets T2, T3, and T4 were statistically similar. The control diet had higher creatinine value, similar to diets T2 and T3 but different from diet T4. Cholesterol value was higher in the control diet similar to diet T2 different from diets T3 and T4. SGOT was higher in the control (diet T1) but differed from diets T2 and T3. SGPT was higher in the control diet, very different from other diets. Though some of the results were inconsistent, total protein, creatinine, cholesterol and SGOT and SGPT were lower in animals fed the supplemented concentrate. Therefore, the results suggest the positive potential of the use of crop residues (cassava peel meal) supplemented with varying levels of AYBM concentrate in the feeding of goats without deleterious effects on blood chemistry.